2015
DOI: 10.1039/c5ta00447k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of poling conditions on the performance of piezoelectric energy harvesters fabricated by wet chemistry

Abstract: The effect of poling conditions on the power output of piezoelectric energy harvesters using sol–gel based Pb(Zr0.53,Ti0.47)O3–Pb(Zn1/3,Nb2/3)O3 piezoelectric thin-films has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…There is one other well-known process to increase the piezoelectric constant of a polymer, namely, poling in a high external electrical field 35 [138][139][140]. It has also been reported that poling improves the piezoelectric properties of piezoceramics [141][142][143]. To facilitate poling and to collect the piezoelectric output voltage, electrodes must be applied.…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
See 1 more Smart Citation
“…There is one other well-known process to increase the piezoelectric constant of a polymer, namely, poling in a high external electrical field 35 [138][139][140]. It has also been reported that poling improves the piezoelectric properties of piezoceramics [141][142][143]. To facilitate poling and to collect the piezoelectric output voltage, electrodes must be applied.…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
“…Recently, E. Nilson et al reported that a strong piezoelectric effect can be achieved for PVDF fibres with a conductive composite based on carbon black and polyethylene using as high a poling voltage as possible and a poling temperature between 60 °C and 120 °C [144]. This can be explained by the heating of the polymer leading to an increase in the mobility of the molecular chain and, thus, a slight reduction in the coercive field and an increase in the charge- ceramics increased significantly as the poling electric field and poling temperature are increased [141][142][143].…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
“…[1][2][3][4] A variety of energy harvesting techniques to collect waste energy from the ambient environment have been extensively studied, such as solar cells for sunlight, thermoelectric devices for gradient heat, and piezoelectric and triboelectric materials for mechanical motion. 5,6 Among them, mechanical sources (e.g. the vibrations of machines, human activities, automobile movement, acoustic waves, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that oxygen vacancies were created after the poling since the ratio of the concentration of oxygen vacancies O V to that of lattice oxygen O L increased from ∼0.12 to ∼0.28 after the poling, as evident in Figure d. It has been reported that the poling process directs the oxygen vacancies toward the surface since the strong electric field reorients the defect dipoles, typically the pairs of cation and oxygen vacancies . With the stabilization of the dipoles under the external bias, more oxygen vacancies were likely positioned near the film surface …”
Section: Resultsmentioning
confidence: 99%